2015
DOI: 10.1142/s1793524515500734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melting heat transfer on peristalsis in the presence of thermal radiation and Joule heating

Abstract: Mathematical model is developed for peristaltic flow of viscous fluid through a compliant wall channel subject to melting heat transfer. Fluid is incompressible and magnetohydrodynamic. Analysis has been performed in the presence of Joule heating and thermal radiation. Solutions for small wave number are obtained. Physical quantities of interest are examined for various parameters of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The non-linearity of the resulting system suggests the application of the perturbation method about the small wave number δ. Thus we get the series form of solutions to plot graphs corresponding to the stream function, temperature, concentration and heat transfer coefficient (Z) as follows (Hayat, Rafiq, et al, 2015):…”
Section: Perturbation Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-linearity of the resulting system suggests the application of the perturbation method about the small wave number δ. Thus we get the series form of solutions to plot graphs corresponding to the stream function, temperature, concentration and heat transfer coefficient (Z) as follows (Hayat, Rafiq, et al, 2015):…”
Section: Perturbation Solutionsmentioning
confidence: 99%
“…In particular, Turkyilmazoglu and Pop (2013) reported heat transfer effects with Jeffery fluid, while Jalil, Asghar, and Imran (2013) found the heat transfer mechanism on the moving surface of a free stream. Hayat, Rafiq, Ahmad, and Yasmin (2015) looked at the impact of melting heat transfer on peristalsis with thermal radiation and Joule heating, and Tripathi (2013) presented a transient heat flow analysis. Further, Ali, Sajid, Javed, and Abbas (2010) examined the heat transfer phenomenon in curved channel, while Sheikholeslami, Hatami, and Ganji (2014) carried out an analysis on nanofluid heat transfer with a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The upper urinary tract consists of the kidney and ureter. The main function of the upper tract is to collect urine and propel urine to the bladder, where urine is stored temporarily and periodically to eliminate waste from the body [3,4]. The pacemaker plays a crucial role in the urinary system by generating the peristalsis wave in the ureter.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the rotational velocity and temperature distributions enhance with an increase in the Reynolds number. Hayat et al [14] employed the perturbation technique to analyze the melting heat transfer of peristaltic flows in the presence of viscous dissipation and Joule heating. They also analyzed the oscillatory heat transfer caused by the sinusoidal traveling wave in a channel.…”
Section: Introductionmentioning
confidence: 99%